Iron Oxide Impregnated Morus alba L. Fruit Peel for Biosorption of Co(II): Biosorption Properties and Mechanism - Janardhan Reddy Koduru; Yoon-Young Chang; Jae-Kyu Yang; Im-Soon Kim (The Scientific World Journal)
Biosorption is an ecofriendly wastewater treatment technique with high efficiency and low operating cost involving simple process for the removal of heavy metal ions from aqueous solution. In the present investigation, Morus alba L. fruit peel powder (MAFP) and iron oxide impregnated Morus alba L. fruit peel powder (IO-MAFP) were prepared and used for treating Co(II) contaminated aqueous solutions. Further the materials were characterized by using FTIR and SEM-EDX analysis. From FT-IR analysis it was found that hydroxyl, methoxy, and carbonyl groups are responsible for Co(II) biosorption. The kinetic data obtained for both biosorbents was well fitted with pseudo-second-order kinetic model. The equilibrium data was in tune with the Langmuir and Freundlich isotherm models. The thermodynamic studies were also carried and it was observed that sorption process was endothermic at 298–328 K. These studies demonstrated that both biosorbents were promising, efficient, economic, and biodegradable sorbents.